STRUCTURE OF THE MEIOFANAL BENTHIC INVERTEBRATES AND USING NEMATODE BIODIVERSITY INDICES IN AN INVEROMENTAL ASSESSMENT ESTUARIES OF BINH DINH PROVINCE, VIETNAM - Tu, Nguyen Dinh; Hien, Nguyen Thanh; Thanh, Nguyen Vu (Vietnam Journal of Marine Science and Technology, 2007)
The fauna of the meiobenthic invertebrates, including marine free-living nematodes, recently has been studying in coastlines and estuarries of Central Vietnam. Present result showed that mostly components of the meiofaunal communities in an investigating zones are Nematodes, Harpacticoida and Polychaeta, among them nematode communities usually consist from 4,95% to 98,98% of total individuals in the sample. Harpacticoida presents in every points of studying area and only annelid Polychaeta has been recognized in two investigated stations, An Du and Thi Nai, with a few density. The nematode density was decreased from the bank transect to the sea transect, but the density of crustacea was opposed, it was increased from the bank to the sea. There are 63 marine nematode species which were firstly described, among them nematode species Chromadorita sp. dominantly occurred in every studied area with 33.2% total individuals in sample, the second dominant species is Axonolaimus sp., which occurred about 18,87% in every studies area. All of recognized nematode species can be divided into four feeding types: selected feeder (1A), non-selected feeder (1B), omnivorous feeder (2A) and predatory feeder (2B). Result showed that selected feeder nematode group occurered only small ration in comparison with other predominant nematode groups 2A and 2B. Thus environmental water quality in An Du and Tam Quan and Thi Nai were became badly. On the other hand, biodiversity nematode indices such as Shanoon index and Margaalef index were not high at every studied points and H’ was valued at 1,2 to 2,2 in Tam Quan and H’ = 0,5 to 2,0 in An Du estuary and H’ was valued at 2,0 to 2,5 in Thi Nai pond. Moreover in the every second (middle) transect of all studied areas, the value of the nematode biodiversity indices were alway higher than its mean in the neighbour first transect and the third transect. Besides, the K-dominance at An Du and Tam Quan and Thi Nai showed that the nematode community here was facing with the negative environmental/actors.